Marriage System in Minangkabau: Interpreting the Concept of Culture Promoted in the Quran - Taufiq, Muhammad; Busyro, Busyro (Islam Transformatif : Journal of Islamic Studies, 2023)
Based on the Minangkabau aphorism, the marriage system in society must refer to the guidance of the Quran and Sunnah, but there are some researchers who say that matrilineal culture, including the marriage system practiced in Minangkabau, is not in line with the values contained in the Quran and Sunnah. The aim of this research is to prove the relationship between the concept of culture in the Quran and the culture of marriage in Minangkabau by asking two questions. First, is the marriage system and culture in Minangkabau in line with the values of marriage in the Quran? Second, what is the relevance of marriage in Minangkabau to the cultural values carried by the Quran? This research is library research using a qualitative approach in the field of interpretation studies, while data analysis uses a comparative method. The results of the study show that there is no fundamental difference between the marriage system adhered to in the Quran and the marriage system practiced by the Minangkabau people and the values promoted by the Quran have been well-cultivated in the marriage process in Minangkabau which has a pivotal to monotheism, in line with human nature, and, produce Islam rahmatan lil alamin.